2010
DOI: 10.1100/tsw.2010.138
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial Cancer Stem Cells

Abstract: There is mounting evidence supporting the idea that tumors, similar to normal adult tissues, arise from a specific stem-like cell population, the cancer stem cells (CSCs), which are considered as the real driving force behind tumor growth, the ability to metastasize, as well as resistance to conventional antitumor therapy. The concept that cancer growth recapitulates normal proliferative and/or regenerative processes, even though in very dysfunctional ways, has tremendous implications for cancer therapy. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 118 publications
(183 reference statements)
0
14
0
Order By: Relevance
“…The tissue-specific stem cells of the normal urothelium have been proposed to reside in the basal layer, responsible for the maintenance of tissue homeostasis and renewal. The basement membrane serves as a nidus for epithelial stromal interactions that are essential for stem cell preservation [ 4 ]. Alternatively, it has also been suggested that at least two independent pools of urothelial stem cells exist [ 1 ].…”
Section: Urothelial Stem Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…The tissue-specific stem cells of the normal urothelium have been proposed to reside in the basal layer, responsible for the maintenance of tissue homeostasis and renewal. The basement membrane serves as a nidus for epithelial stromal interactions that are essential for stem cell preservation [ 4 ]. Alternatively, it has also been suggested that at least two independent pools of urothelial stem cells exist [ 1 ].…”
Section: Urothelial Stem Cellsmentioning
confidence: 99%
“…Several stem cell markers have been found to be linked to recurrence or progression. One example is the CD44v8-10-to-standard CD44-ratio (total ratio of all CD44 alternative splicing isoforms) in urothelial cancer that has been shown to be closely associated with tumor progression and aggressiveness [ 4 , 30 ]. ALDH1, has also been reported to be associated with BCSCs and a worse prognosis in a large number of studies [ 31 , 32 ].…”
Section: Csc As Markers Of Progressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adhesion molecules are cell surface glycoproteins mediating cellcell and cell-matrix interactions. CD44 positive cells are located in the basal layer of the normal urothelium as well as in urothelial cell carcinoma (Dimov et al, 2010). CD44 standard (CD44s) is a member of the immunoglobulin superfamily, involved in cell-cell and cell-matrix interactions.…”
Section: Introductionmentioning
confidence: 99%